O estágio na licenciatura em matemática : um espaço de formação compartilhada de professores - Andrade, José Antônio Araújo (2012)
The main objective of this research was to analyze the potential of a work shared between current and future Mathematics teachers. The focus of this research is the learning of teaching, which is established by the relation with the knowledge, or in this case, with the knowledge mobilized in the context of pedagogic practices. The following problematic were formulated: which knowledge is mobilized and/or (trans)formed on learning of teaching in a context of shared work? Which elements act or make possible the learning of teaching and professional development in a context of shared work? The option was to investigate an experience of shared work through written or oral narratives. Data collection was done during the school year of 2009. Twenty one students of graduation, ten collaborator professors and the advisor/researcher took part in this research. Ten work teams were constituted, which compounded the investigation scenario. The following aspects were analyzed: the reflexive process of graduation students during their participation and learning while teaching Mathematics in the scholar context, the possibilities and potential of collaborative work for the teacher formation through the internship and for the consolidation of the teaching profession, the knowledge and reflection initiated in this process, and the contributions for the supervised internship for the continuing formation and for Scholar Mathematics ideas of these actors. The analysis of the content allowed us to establish four meaning units: professionalization; learning of teaching; tensions and contradictions, and cultural confrontations (relationship university school). It is necessary to consider that from this four meaning units, the first two were took as categories of analysis. In these units it was possible to note the formation potential on the constitution of multiple learning. An identity process was established between the trainees and the profession in the reflection moments about practices with which they started interacting. Diverse knowledge was mobilized, which culminated on the learning related to: curriculum management in Mathematics (classes planning and their conduction guided by an investigative and problematizing posture; the meaning of evaluative processes; the importance of interactions in classroom for the establishment of a learning environment for the students). Moreover, it was possible to identify important aspects of the professional development of the supervisor teacher, which characterize the beginning of her self-management in relation to her formation process. This research allowed us to glimpse a new course for internship activities in which the relationship between university and school is strengthened in order to look for possibilities or strategies that look for the better interaction among the subjects of these activities, thinking that the evolution of teaching professionalization depends on an initial formation that provides autonomy to the subject management of its own professional practices.